A Stowaway Mission to the Moon. - Romero, J.J.
Several months from now, the empty upper stage of an Atlas V rocket will slam into a shadowy crater near the north pole of the moon, tossing a plume of debris up into the sunlight. By then, the Atlas V will have delivered its main payload, the Lunar Reconnaissance Orbiter (LRO), and a smaller stowaway. That stowaway satellite will watch the spectacle unfold from above, looking for telltale signs that thereÃ?Â¿s water in the lunar soil, before it, too, crashes into the moon.